2016
DOI: 10.1016/j.tecto.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Rock uplift at the transition from flat-slab to normal subduction: The Kenai Mountains, Southeast Alaska

Abstract: The process of flat-slab subduction results in complex deformation of overlying forearcs, yet how this deformation decays with distance away from the zone of underthrusting is not well understood. In south central Alaska, flat-slab subduction of the Yakutat microplate drives shortening and rock uplift in a broad coastal orogenic belt. Defined limits of the zone of underthrusting allow testing how orogenesis responds to the transition from flat slab to normal subduction. To better understand forearc deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 78 publications
(145 reference statements)
3
12
0
Order By: Relevance
“…In addition, the large coseismic slip area between the Kenai Peninsula and the Montague Island shows a localized low‐Vs and high‐ν anomaly in the overriding plate. Focused and rapid exhumation has taken place around the Montague Island as revealed by young apatite (U‐Th)/He ages of <5 Ma, especially in the southwestern island (Arkle et al, ; Ferguson et al, ; Valentino et al, ). Haeussler et al () suggested that several splay faults there have accommodated the exhumation and rooted into the megathrust where there is probably underplating.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the large coseismic slip area between the Kenai Peninsula and the Montague Island shows a localized low‐Vs and high‐ν anomaly in the overriding plate. Focused and rapid exhumation has taken place around the Montague Island as revealed by young apatite (U‐Th)/He ages of <5 Ma, especially in the southwestern island (Arkle et al, ; Ferguson et al, ; Valentino et al, ). Haeussler et al () suggested that several splay faults there have accommodated the exhumation and rooted into the megathrust where there is probably underplating.…”
Section: Discussionmentioning
confidence: 99%
“…Axial fluvial systems with an eastern provenance also migrated to the area adjacent to the southern Kenai Peninsula (CB‐23) during middle Miocene time. Apatite thermochronologic ages <20 Ma in the northern Kenai Peninsula and Talkeetna Mountains indicate exhumation of the eastern region during the Miocene [ Little and Naeser , 1991; Hoffman and Armstrong , ; Arkle et al ., ; Valentino et al ., ]. The eastern provenance region sits above the shallow part of the Yakutat slab (Figure a) and exhumation may have resulted from insertion of the slab [ Finzel et al ., ; Arkle et al ., ; Valentino et al ., ].…”
Section: Paleogeographic and Tectonic Implicationsmentioning
confidence: 99%
“…Furthermore, previous studies have demonstrated that very little sand‐sized sediment is recycled from the Paleozoic and Mesozoic strata in the northern region [ Finzel et al ., ; Lease et al ., ]. In contrast, exhumation of the eastern region, especially the western Chugach Mountains located above the flat‐slab, continued into late Miocene time [ Buscher et al ., ; Arkle et al ., ; Valentino et al ., ]. Therefore, uplift and erosion of the eastern region resulted in the dominance of an eastern provenance for almost the entire fore‐arc basin during late Miocene time, with an additional small contribution from plutonic rocks in the northern region.…”
Section: Paleogeographic and Tectonic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations